Isolated muscle hypertrophy as a sign of radicular or peripheral nerve injury. Issue 4 (April 1991) - Mattle, H P; Hess, C W; Ludin, H P; Mumenthaler, M
Abstract : Two patients with isolated neurogenic hypertrophy of the trapezius muscle due to accessory nerve injury and a patient with neurogenic hypertrophy of the anterior tibial muscle due to chronic radicular lesion L4 are described. Electromyography of the affected muscles showed dense continuing spontaneous discharges of complex potentials. Muscle biopsy performed in two patients showed abundant hypertrophic muscle fibres, identified in one case by ATP-ase reaction as being of predominantly type I. In the majority of previously reported patients with neurogenic muscle hypertrophy confined to the calf muscle, a passive stretch mechanism was suggested as a cause of the hypertrophy. It is assumed that the excessive spontaneous muscle activity gave rise to the hypertrophy in these patients. This may also be true in previously reported patients with neurogenic hypertrophy and similar spontaneous activity in electromyography.